2015
DOI: 10.1016/j.jctube.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

How to manage children who have come into contact with patients affected by tuberculosis

Abstract: Childhood tuberculosis (TB) indicates a recent infection, particularly in children aged < 5 years, and therefore is considered a sentinel event insofar as it highlights the presence of an undiagnosed or untreated source case. The risk of acquiring TB is directly proportional to the number of bacilli to which a subject is exposed and the environment in which the contact occurred. This document contains the recommendations of a group of Italian scientific societies for managing a child exposed to a case of TB ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…However, caution in the use of IGRAs in children is based on the potentially immature immune system of infants which might not be capable of responding properly to antigenic stimuli ex vivo (15). Current evidence does not support the use of QFT-IT as an alternative to TST; however, different national guidelines recommend IGRAs in addition to TST in screening algorithms for TB infection (3,24,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, caution in the use of IGRAs in children is based on the potentially immature immune system of infants which might not be capable of responding properly to antigenic stimuli ex vivo (15). Current evidence does not support the use of QFT-IT as an alternative to TST; however, different national guidelines recommend IGRAs in addition to TST in screening algorithms for TB infection (3,24,35).…”
Section: Discussionmentioning
confidence: 99%
“…Children were categorized as TB excluded if, after undergoing QFT-IT based on signs and symptoms suggestive of TB, active disease was excluded and another diagnosis was made at the end of investigation and treatment. According to Italian pediatric TB recommendations (24), before admission to school, children in contact with adults with active tuberculosis, children who had recently arrived from an area where TB is endemic, and those undergoing immunosuppressive therapy were referred to the Pediatric Unit and underwent a medical history investigation including BCG vaccination status, clinical assessment, chest X-ray, and immunological and microbiological assays. After exclusion of active TB, children were categorized at the first investigation and after 3 months as having LTBI based on the physician's decision after evaluating QFT-IT and TST results, risk of exposure, BCG status, and origin.…”
Section: Methodsmentioning
confidence: 99%
“…25 Transaminase levels more than five times the normal upper limit are considered a sign of hepatotoxicity, and IPT should be discontinued. 7 There is no universally accepted threshold to describe hyperuricemia in children and adolescents. 26 In children, hyperuricemia is generally defined as a SUA level of >7 mg/dL and may result from overproduction or underexcretion of uric acid.…”
Section: Discussionmentioning
confidence: 99%
“…In older children and adolescents, if TST and IGRA are positive and chest X-ray is negative, IPTshould continue for 6 to 9 months. 4,7 Isoniazid is an essential drug in the chemotherapy of TB. Isoniazid for 6 to 9 months is the most widely used form of TB preventive treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Children who live in smokers are also more at risk of Tb infection (Laghari et al, 2019). The family plays a critical role in preventing the transmission of Tb to children (Lancella et al, 2015). Previous analysis showed that some variables were found to be insignificant because of the existence of other variables that were probable to play a role (Nurjana, Gunawan, & Tjandrarini, 2019).…”
Section: Introductionmentioning
confidence: 99%